The intellectual labor as the phenomenon of the social production and its social consequences - Briukhovetskyi, Mykola (Actual Problems of Mind, 2017)
The paper presents the problem of intellectual labor as a new type of labor in the information society. The social consequences of the spread of intellectual labor are analized by focusing on the tendency of changing the traditional motivation and leveling exploitation.